Date palm micropropagation: Advances and applications - Al-Khayri,Jameel Mohammed (2017)
ABSTRACT Date palm (Phoenix dactylifera L.) is a fruit tree resilient to adverse climatic conditions predominating in hot arid regions of the Middle East and North Africa. The date fruit contains numerous chemical components that possess high nutritional and medicinal values. Traditional propagation by offshoots is inefficient to satisfy current demands for date palm trees. Alternatively, micropropagation provides an efficient means for large-scale propagation of date palm cultivars. Both somatic embryogenesis and organogenesis, either directly or indirectly though the callus phase, have been demonstrated in date palm in vitro regeneration. Culture initiation commonly utilizes shoot-tip explants isolated from young offshoots. Recently, the immature inflorescences of adult trees were utilized as an alternative nondestructive source of explants. In addition to the nature of the explant used, successful plant regeneration depends on the cultivar, composition of the culture medium and physical status. Challenges of date palm micropropagation include long in vitro cycle, latent contamination, browning, somaclonal variation as well as ex vitro acclimatization and transplanting. A remarkable amount of research investigating these factors has led to optimized protocols for the micropropagation of numerous commercially important cultivars. This has encouraged the development of several international commercial tissue culture laboratories. Molecular characterization provides an assurance of genetic conformity of regenerated plantlets, a key feature for commercial production. This article describes date palm micropropagation protocols and also discusses recent achievements with respect to somaclonal variation, molecular markers, cryopreservation and future prospects.